Exploring Vaccine Hesitancy Levels Among Turkish Parents in 2024 After Pandemic; Key Influencing Factors: A Cross-Sectional Study - Zehra Kılınç; Songül Beycur Işık (International Journal of Clinical Practice)
Conclusions: In this study, vaccine hesitation was found in 16.8% of the parents and the level of hesitation was found to be associated with knowledge and education levels. The hesitation rate was found to be lower in parents who had sufficient knowledge about childhood vaccines. The higher hesitation levels of parents who reported that the pandemic did not negatively affect their vaccination decisions suggest the effect of social and psychological factors. The findings emphasize the importance of education and awareness-raising activities for parents to reduce vaccine hesitancy.